Barriers to services at the intersection of child maltreatment and domestic violence: a multi-perspective analysis of parents with lived experience and professionals - Banda, Linda Chimwemwe (Journal of family violence, 2024)
Purpose: Firm evidence exists on the co-existence of child maltreatment and domestic violence (DV). This study examines the barriers to service delivery for families experiencing DV who are child welfare (CW) system involved from the perspectives of two key groups: parents with lived experience of DV and CW and multi-sector professionals. Methods: A thematic content analysis was conducted of data from 16 in-person and remote listening sessions of 140 participants including families and DV/CW professionals across the U.S. Results: Findings suggest that for parent participants communication, inadequate services, lack of trust, and providers not serving families well were some of the challenges that impact accessing and receiving services and resources. Professional participants described the limited availability of services, systemic challenges, and collaboration as barriers impacting the access to and provision of resources to families experiencing DV and involved within the CW system. Conclusions: Discussion points reflect on the synergies and divergencies in the participant groups’ identified barriers. Study implications emphasize the need to address the challenges encountered by CW and DV systems at the individual, systemic and educational levels.